The 3ʹ region length polymorphism of clfa gene in staphylococcus aureus clinical samples isolated from three hospitals in Qom city - reza yari; Mohammad Reza Mehrabi; Fatemeh Mohammad Salehi (بیولوژی کاربردی, 2018)
Introduction: Staphylococcus aureus produce enzymes and various toxins for survival, protein, carbohydrate, lipid and Nucleic acid degradation, drug resistance, attachment to host cells and pathogenicity. One of the most important of surface bacterial virulence factors is clumping factor or Clf A. It protein cause to connect bacteria- Fibrinogen host cell. The aim of this study was to investigate the existence and possible variations in the 3'-end of clf A gene. Materials & Methods: 100 clinical strains isolated from Nekuei(Hedayati), Kamkar(Arabnia) and Shahid Beheshti hospitals were selected after confirmation by microbial, biochemical and molecular 16 srRNA tests. A pair of primers for amplification of variable region genes were used. Results: All strains isolated from three hospitals in Qom city produced 1100 bp amplicons size. The amplicons are sent to the relevant company for sequencing and comparison with standard sequence. Conclusion: According to other studies that were produced 900 to 1000 bp amplicons size by the same primers this is the first report of a gene polymorphism in 3'-end of clf A gene in the world. In this area reported 18 nucleotide minisatellite repeats which causes errors in the DNA replication by DNA polymerase as Replication Slippage. This event has been led to the creation and distribution of new version of the gene in the city of Qom. This study needs further investigation about sequence and encoded protein.